Evolution of Autonomous Selfing in Marginal Habitats: Spatiotemporal Variation in the Floral Traits of the Distylous Primula wannanensis - Zhang, Wei; Hu, Ying Feng; He, Xiao; Zhou, Wei; Shao, Jian Wen (Frontiers in Plant Science, 2021)
Outcrossing plant species are more likely to exhibit autonomous selfing in marginal habitats to ensure reproduction under conditions of limited pollinator and/or mate availability. Distyly is a classical paradigm that promotes outcrossing, however, little is known about the variation in floral traits associated with distylous syndrome in marginal populations. In this study, we compared the variation in floral traits including stigma and anther height, corolla tube length, herkogamy and corolla diameter between the central and peripheral populations of the distylous species Primula wannanensis, and assessed the variation of floral traits at early and late florescence stages for each population. To evaluate the potential consequences of the variation in floral traits on the mating system, we investigated seed set in each population under both open-pollinated and pollinator-excluded conditions. The flower size of both short- and long-styled morphs was significantly reduced in late-opening flowers compared with early-opening flowers in both central and peripheral populations. Sex-organ reciprocity was perfect in early-opening flowers, however, it was largely weakened in the late-opening flowers of peripheral populations compared with central populations. Of this flowers, disproportionate change in stigma height (elongated in S-morph and shortened in L-morph) was the main cause of reduced herkogamy, and seed set was fairly high under pollinator-excluded conditions. Our results provide empirical support for the hypothesis on evolution of delayed autonomous selfing in marginal populations of distylous species. Unsatisfactory pollinator service is likely to have promoted reproductive assurance of distylous plants with largely reduced herkogamy mimicking ‘homostyles’.